Portal web para la unidad educativa Gladys Flores Macías en la ciudad de Guaranda, incorporando chatbot, año 2023 - León Ramos, Ismael Sebastian (2024)
The objective of this work was to develop a web portal for the Educational Unit "Gladys Flores Macias" in the city of Guaranda, incorporating the ChatBot. Using the documentary-bibliographic methodology to know the current situation of the institution and also for the realization of the portal we used the External Programming methodology that helped us to carry out the work through phases that indicates the same and fully comply with the work, this methodology meets 5 important phases which are: Planning, Design, Coding, Testing and finally the launch of the web portal, it also worked for the incorporation of the chatbot. Obtaining as a result the development of a functional, portable and robust web portal, which was carried out with the help of the XP methodology (External Programming) allowing through its faces to structure in a better way the web portal of the Educational Unit "Gladys Flores Macias" Concluding that the chatbot incorporated is in adequate functionality that allows a synchronous communication with the different users that access the portal, having immediate answers to solve any general doubt of the institution. Recommending the institution to give continuous maintenance to the Web portal as it will allow better communication between the different strata of the educational unit as long as the page is updated and functional. Keywords: Web Portal, Chatbot, External Programming, Virtual Assistant